2014
DOI: 10.5152/jaem.2014.075
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Patients Admitted to the Emergency Department Due to Complications Related to Warfarin Treatment

Abstract: Objective: Warfarin is the most commonly used oral anticoagulant around the world. The most important complication of warfarin is bleeding. This study was conducted to evaluate the patients who were admitted to our emergency department due to complications related to warfarin treatment. Material and Methods:Eighty-nine patients (32 females, 57 males) were enrolled into this retrospective study. The patients were evaluated according to their age, gender, duration of therapy (year), co-administered drugs, bleedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…In our study, the mean age of the patients was 64.9 ± 14.5 years and the rate of bleeding complications in those ≥ 65 years of age was 56.3%. However, while several studies have reported that advanced age is a risk factor for major bleeding [13, 16, 21, 22], this has not been consistently demonstrated [15, 17]. In our study, bleeding complications occurred in 26.2% of patients < 65 years of age and in 38.9% of patients ≥ 65 years of age.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…In our study, the mean age of the patients was 64.9 ± 14.5 years and the rate of bleeding complications in those ≥ 65 years of age was 56.3%. However, while several studies have reported that advanced age is a risk factor for major bleeding [13, 16, 21, 22], this has not been consistently demonstrated [15, 17]. In our study, bleeding complications occurred in 26.2% of patients < 65 years of age and in 38.9% of patients ≥ 65 years of age.…”
Section: Discussioncontrasting
confidence: 76%
“…Eroglu et al [12] reported that, among warfarin users seen in the hospital, bleeding most often occurs in the gastrointestinal system (38.5%) and especially in the upper gastrointestinal tract (n = 83). In the study of Sayhan et al [13], melena-hematochezia (16.9%), hematuria (14.6%), and cyanosis of the skin (10.1%) were the most common presenting complaints among patients admitted to the ED for warfarin-associated complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are in line with other studies on the subject. 8,10,12,14,16,17 Gastrointestinal bleeding site was a predictor of hospitalization, probably due to its higher severity and the need for diagnostic or therapeutic endoscopic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies reporting the prevalence and management of hemorrhagic complications (such as stroke) in emergency services are scarce, with high methodological heterogeneity. [10][11][12][13][14][15] To date, there is little knowledge about the reasons of hospitalization among these patients. Thus, this study aims to evaluate the Recommendations for conducting cross-sectional studies were followed according to the STROBE Statement (https://www.strobe-statement.org).…”
Section: Introductionmentioning
confidence: 99%